The geopolitics of research funding in Europe and the USA: some policy aspects. (4th August 2014) - Higgins, Tom
In Europe, research has concentrated in the largest countries, and the criterion of excellence as a yardstick for support accelerates this trend. In the USA, a parallel concentration of scientific resources in the top universities is institutionalized. These technology gaps are larger than the economic gaps between the more developed and the poorer regions, and are reflected in economic and social development indices. The use of central programs to redistribute technological development capability is described in the context of the US and EC programs EPSCOR and STRIDE. A strong research university is seen as a first step in bringing development to a region, and allowing new entrants to participate in front–line R&D.